2021
DOI: 10.1093/biolinnean/blab011
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic response to a major hurricane in Anolis lizards in urban and forest habitats

Abstract: Little is known about the synergistic impacts of urbanization and hurricanes on synanthropes. We compared morphological traits of the lizard Anolis cristatellus on Puerto Rico sampled before the 2017 category 5 Hurricane Maria and 4 and 11 months after the hurricane. We measured limb lengths, toepad size and the number of subdigital scales, termed lamellae, that facilitate adhesion. We hypothesized that the hurricane should have selected for longer limbs and larger toepads with more lamellae, which are traits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 62 publications
1
8
1
Order By: Relevance
“…Therefore, the potential for toepad size to follow the predictions of the hypothesis remains to be tested. Nevertheless, toepad size in A. cristatelus in forest habitats in Puerto Rico decreased four months after the hurricane, a pattern contrary to that predicted by the hypothesis [17].…”
Section: Discussioncontrasting
confidence: 85%
See 2 more Smart Citations
“…Therefore, the potential for toepad size to follow the predictions of the hypothesis remains to be tested. Nevertheless, toepad size in A. cristatelus in forest habitats in Puerto Rico decreased four months after the hurricane, a pattern contrary to that predicted by the hypothesis [17].…”
Section: Discussioncontrasting
confidence: 85%
“…Our analyses in a shade-specialist in Puerto Rico do not support this hypothesis. Similarly, a study quantifying traits of A. cristatellus —an open/disturbed area specialist — before and after hurricane disturbance also found no support for phenotypic changes that favour clinging ability [17]. What can explain this contrasting result on studies following the same hurricane disturbances in different islands?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results from recent studies of hurricane‐induced selection (Donihue et al, 2018) and phenotypic shifts (Aviles‐Rodriguez et al, 2021; Dufour et al, 2019; Fokidis & Brock, 2020; Rabe et al, 2020) provided the impetus for our experiments, which were designed to investigate the ecological and functional relationships that influence clinging performance as well as how behaviour might affect the ability of lizards to survive hurricanes. Our experiments showed that clinging force based on the physical ability of lizards did not predict clinging ability when experiencing the more realistic conditions of hurricane‐force winds.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies show selective mortality based on morphological trait variation; for example, using comparisons of preand post-hurricane populations, Donihue et al (2018) found that natural selection favoured lizards with larger toepads and longer forelimbs, trait values that enhance clinging ability in anoles (Elstrott & Irschick, 2004;Kolbe, 2015), as well as shorter hindlimbs that reduce aerodynamic drag and improve the clinging ability of lizards (Debaere et al, 2021). Several other studies have reported changes in performance, behaviour and morphology of anole populations after hurricanes (Aviles-Rodriguez et al, 2021;Dufour et al, 2019;Fokidis & Brock, 2020;Rabe et al, 2020). The limb and toepad morphology of lizards surviving hurricanes is mostly consistent with survivors having greater clinging performance (Debaere et al, 2021;Elstrott & Irschick, 2004, but see Aviles-Rodriguez et al, 2021), pointing to the likely functional relationship underlying the observed selection.…”
Section: Introductionmentioning
confidence: 99%